The community structure of mangroves in Barangay Mag-aba, Pandan, Antique. - Villanueva, Ma. Aimy Donesa
This study aims to assess the community structure of mangroves in Brgy. Mag-aba, Pandan, Antique using transect line plot method. specifically it aims to: 1. determine selected physical and chemical factors such as salinity, pH, temperate for water and soil as well as characterization of substrates; 2. identify and classify the mangrove species present in the area. 3. describe the community structure in terms of Stand Basal Area, Stems Per hectare, Relative Density, Relative Frequency, Relative Dominance, Importance Value, Shannon--Index of Diversity (or other indices used), Zonation Patterns, Seedlings and Sampling Density. Thirteen true mangroves were observed in the site belonging to 9 families. Family Rhizoporaceae was the most represented with four representative species which were Bruguiera cylindrica, Bruguiera gymnorrhiza, Rhizopora apiculata and Rhizopora mucronata. The rest were also fully represented. The following were the rest of the families and their respective representative species: Family Avicenniacea-Avicennia marina, Family Combretaceae- Lumnitzera littorea and Lumnitzera racemosa, Family Euphorbiaceae- Excoecaria agallocha, Family Meliceae- Xylocarpos granatum, Family Myrsinaceae- Aegiceras corniculatum, Family Palmae- Nypa fruticans, Family Sterculiaceae- Heritiera littoralis, and Family Sonneratiaceae- Sonneratia alba. Basal area ranged from 0.032m squared/ha for Rhizopora mucronata to 40.777 m2/ha for Sonneratia alba. The species with the highest average stems per hectare recorded was Nypa fruiticans with 5439. The species having the lowest average stems per hectare was Rhizopora mucronata with 40. The species with the highest average relative density was Nypa fruiticans with 123.846 trees per hectare. Nypa fruiticans was in almost all the sites surveyed with 74.603% occurence. The species with the lowest frequency of occurence was Rhizopora mucronata10.317%. Sonneratia alba had the highest relative dominance (37.456). The species with the least relative dominance was Rhizopora mucronata (0.032). The most important species was Nypa fruiticans (98.560). The least was Rhizopora mucronata (2.466). The area is considered to be diverse at 0.7426. while on a per station basis, Station 2 had the highest at 0.9695 and the least was in Station 2 at 0.3143. Station 1 had a 0.9442 Index of Diversity. The study area shows a certain degree of zonation from seaward to landward. Avicennia marina and Rhizopora apiculata was found to occupy the seaward zone but Avicennia marina was the most abundant. In the middlezone, there were Bruguiera cylindrica and Bruguiera gymmorrhiza. Landward, species like Xylocarpos granatum, heritiera littoralis, Lumnitzera littorea and Lumnitzera racemosa were recorded to occupy that area. Nypa fruiticans were distributed in any of the zones. sonneratia alba was observed to occupy the riverine zone together with Avicennia marina and Rhizopora apiculata. Among the 13 species recorded during the sampling, Avicennia marina has the highest seedling count at 398. The species with the least was Rhizopora mucronata (1). Bruguiera cylindrica had the highest sampling density at 80 and the least was Rhizophora apiculata at 13.